Dagtilbudsledelse – en profession in spe? - Bøje, Jakob Ditlev; Wiedemann, Finn (Tidsskrift for Professionsstudier, 2025)
The article discusses the professionalization of early childhood education leadership based on the research question: To what extent and how can early childhood education leadership be characterized as a profession in the making? The question is discussed based on the criteria that traditionally define professions, namely education, independently developed knowledge base, authorization and autonomy in work, a specific professional language, and ethical code. Throughout the article, parallels are drawn to the field of school leadership. The article argues that if one adopts a professional theoretical perspective on early childhood education leadership, it can be observed that several of the conditions that traditionally define a profession are also present within the field of early childhood education leadership. However, professionalization is less advanced compared to the field of school leadership. In early childhood education leadership, we are more dealing with leaders of a profession than with so-called professional leaders, i.e., leaders who are removed from the operational everyday life.